TOXICITY OF ETHANOL EXTRACT OF PELAWAN LEAVES (TRISTANIOPSIS OBOVATA Benn.) ON THE HEMATOLOGICAL PROFILE OF WHITE RATS (RATTUS NORVEGICUS L.) - Yusfiati, Yusfiati; Sari Marwan, Avilia Dayang; Husadha, Azura (Universitas Medan Area, 2024)
Tristaniopsis obovata Benn. is one of the herbal plants that contains phenolics flavonoids, saponins, tannins and steroids/triterpenoids. The secondary metabolites are known to have antioxidant activity and toxicity that can affect hematological profiles. This study aims to determine the toxicity effects of ethanol extract of T. obovata Benn. leaves on LD50 value, erythrocyte morphology, and hematological profile in white rats. The study used a Complete Randomized Design (CRD) with 4 treatments and 4 repeats. The treatment consisted of P0 (control), P1 (dose of 300 mg/kg body weight) (P1), P2 (dose of 2000 mg/kg body weight), and P3 (dose of 5000 mg/kg body weight). LD50 calculation using AOT 425 StatPgm software and hematological profile analysis using ANOVA. The results showed LD50 value of T. obovata Benn. leaf extract. was 1.750 mg/kg BW as mild toxic. The morphology of P2 erythrocytes shows abnormal form anisocytosis and P3 form Burr cells and macrocytosis. The administration of extract in all treatments was not significant from the number of erythrocytes, leukocytes and hemoglobin comcentration of white rats.